Synergistic enhancement of hydrophobic dental adhesives: autonomous strengthening, polymerization kinetics, and hydrolytic resistance - Burak Korkmaz; Erhan Demirel; Qiang Ye; Qiang Ye; Anil Misra; Anil Misra; Candan Tamerler; Candan Tamerler; Candan Tamerler; Paulette Spencer; Paulette Spencer; Paulette Spencer (Frontiers in Dental Medicine)
The leading cause of composite restoration failure is recurrent marginal decay. The margin between the composite and tooth is initially sealed by a low-viscosity adhesive, but chemical, physical, and mechanical stresses work synergistically and simultaneously to degrade the adhesive, destroying the interfacial seal and providing an ideal environment for bacteria to proliferate. Our group has been developing self-strengthening adhesives with improved chemical and mechanical characteristics. This paper reports a self-strengthening adhesive formulation that resists hydrolysis-mediated degradation by providing intrinsic reinforcement of the polymer network through synergistic stimulation of free-radical polymerization, sol-gel reaction, and hydrophobicity. Hydrophobic resin formulation (NE1) was developed using HEMA/BisGMA 28/55w/w and 15 wt% MPS. Control (NC1) contained HEMA/BisGMA 28/55 w/w and 15 wt% MES. The polymerization kinetics, water sorption, leachates, and dynamic mechanical properties of the resin samples were investigated. The NC1 and NE1 samples showed comparable polymerization kinetics, degrees of conversion and water sorption. In contrast, NC1 showed significantly higher levels of HEMA and BisGMA leachate, indicating faster degradation in ethanol. At day 3, cumulative HEMA leachate for NC1 was ten times greater than NE1 (p < 0.05). Dynamic mechanical properties were measured at 37 and 70°C in both dry and wet conditions. Under dry conditions, the storage moduli of NC1 and NE1 were comparable and the glass transition temperature (Tg) of NC1 was statistically significantly lower (p < 0.001) than NE1. Under wet conditions, the storage modulus of NC1 was lower than NE1 and at 70°C there was a threefold difference in storage modulus. At this temperature and under wet conditions, the storage modulus of NC1 is statistically significantly lower (p < 0.001) than NE1. The results indicated that in the wet environment, NE1 provided lower chain mobility, higher crosslink density, and more hydrogen bonds. The newly formulated methacrylate-based adhesive capitalizes on free-radical polymerization, sol-gel reactions, and hydrophobicity to provide enhanced mechanical properties at elevated temperatures in wet environments and hydrolytic stability under aggressive aging conditions.